2010
DOI: 10.2106/jbjs.i.00457
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted and Robot-Assisted Technologies to Improve Bone-Cutting Accuracy When Integrated with a Freehand Process Using an Oscillating Saw

Abstract: Significant improvements in cutting accuracy can be achieved when a navigation system or an industrial robot is integrated into a freehand bone-cutting process when no jigs are available. The procedure for navigated hand-controlled positioning of the oscillating saw appears to be easy to learn and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…The results of the study discussed here concur with those of previous laboratory experiments [27] that assessed quantitatively the advantages of using navigation technology to perform bone cutting. The previous study was designed independently of any surgical application and used synthetic bones of simple rectangular geometry.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the study discussed here concur with those of previous laboratory experiments [27] that assessed quantitatively the advantages of using navigation technology to perform bone cutting. The previous study was designed independently of any surgical application and used synthetic bones of simple rectangular geometry.…”
Section: Discussionsupporting
confidence: 88%
“…The 3D CT model of the hemipelvic bone was loaded into the system. The spine module of the navigation system was adapted for direct navigation of the oscillating saw blade [27].…”
Section: Navigated Bone Cutsmentioning
confidence: 99%
See 1 more Smart Citation
“…8). When jigs are not available, a significant improvement in cutting accuracy can be achieved using a navigating system or an industrial robot that is integrated into the freehand bone-cutting (Cartiaux et al, 2010). We open the oblique osteotomy stepwise using three stacked osteotomes and a calibrated wedge spreader.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In addition, reconstruction correlations between host-graft junction parameters were found to be poor [4]. A subsequent geometrical model study by Cartiaux et al demonstrated that improvements in cutting accuracy could be achieved when CAOS was integrated into a freehand bone-cutting process [5].…”
Section: Introductionmentioning
confidence: 99%